Efektivitas Sanksi Pidana Bagi Pelaku Pelanggaran Lalu Lintas di Kabupaten Tabanan - I Gede Made Widia Permana; Anak Agung Sagung Laksmi Dewi; Made Minggu Widyantara (Warmadewa Press, 2022)
Traffic violations are the cause of most traffic accidents. Efforts to reduce violations in a persuasive way seem very complex and cannot be handled properly and correctly by one agency, namely the police, so good coordination between agencies are needed to optimize repressive traffic law enforcement. This research aims to determine the effectiveness of criminal sanctions for traffic violations in Tabanan Regency. The type of research in the writing of this scientific paper is an empirical legal research type, with data sources categorized as primary and secondary. Data were collected by observation, interviews and literature review and then analyzed descriptively. In raising the problem, it uses qualitative data analysis which is applied descriptively. Perpetrators of traffic violations in the Tabanan Police jurisdiction are still relatively high because the level of public awareness in traffic order is still lacking. The effectiveness of the imposition of criminal sanctions for traffic order violators in Tabanan Regency is still not effective.